Implementation of Wireless Xbee Autentication System of Motorcycle - Marchel Thimoty Tombeng; Andrew Andreas Taghulihi; Jacquline M. S. Waworundeng (CogITo Smart Journal, 2019)
The increase of two-wheeled vehicles in Indonesia can be identified as a primary need for the community, which is directly proportional to the number of population of vehicles in Indonesia which has increased every year, and the crime rate in two-wheeled vehicles has increased from year to year. This phenomenon involves many parties creating and developing various types of technology and systems to reduce the impact of crime on two-wheeled vehicles. In designing and developing this system, the researchers integrates several modules including Arduino Mega 2560, Arduino Uno, RFID implants, and Wireless Xbee which perform wireless communication tool between the two microcontrollers. The modules are integrated into a digital module to replace the conventional system for turning on and off the motorcycle’s engine. By using the prototyping process model the development of this system can be enhance or developed more in future to improve the security system on motorcycle vehicles.